Immunologic assessments from ARTEMIS: A European, phase 3, randomized, double-blind, placebo-controlled trial of AR101 in peanut-allergic subjects aged 4–17 years - Delebarre Sauvage, C.; Nilsson, C.; Beyer, K.; Fernández-Rivas, M.; du Toit, G.; Turner, P.J.; Blümchen, K.; Dolores Ibáñez, M.; Deschildre, A.; Muraro, A.; Sharma, V.; Erlewyn-Lajeunesse, M.; et al. (REVUE FRANCAISE D'ALLERGOLOGIE ET D'IMMUNOLOGIE CLINIQUE, 2021)
In ARTEMIS, 58% of AR101-treated subjects vs. 2% of placebo-treated subjects tolerated 1000mg peanut protein as a single dose at exit double-blind, placebo-controlled food challenge (DBPCFC; P<0.0001) following treatment with AR101, an investigational oral biologic drug product for peanut oral immunotherapy. Immune responses to AR101 were assessed at 3 timepoints and compared with the placebo treatment group. All enrolled subjects had a clinical history of peanut allergy, demonstrated sensitization to peanut (skin prick test [SPT] mean wheal diameter ≥3mm and/or peanut-specific immunoglobulin E [psIgE] ≥0.35kUA/L), and reacted to ≤300mg peanut protein at screening DBPCFC. SPT wheal diameter (mm), psIgE (kUA/L) and psIgG4 (mgA/L) assessments were performed at screening, end of dose escalation and study completion (following 3 months at 300mg/day). Differences between treatment groups from screening to exit were analyzed using an ANCOVA model with terms fitted for group, country and screening value. A total of 175 ARTEMIS subjects (AR101 n=132, placebo n=43) were treated. SPT wheal diameter, psIgE levels, psIgG4 levels and psIgE/IgG4 ratio are summarized in Table 1. From baseline to exit (AR101 vs. placebo), psIgG4 levels increased (P<0.0001); SPT wheal diameter (P<0.0001) and psIgE/psIgG4 (P<0.0001) decreased. In AR101-treated subjects, psIgE levels 2 increased at the end of dose escalation and decreased back to baseline levels, with no change between treatment groups (P=0.6089) from baseline to exit. Exposure to AR101 was associated with immunologic changes consistent with immunomodulation: increased psIgG4, decreased peanut SPT wheal size and transient changes in psIgE levels, as reported in previous peanut oral immunotherapy trials.